PENGARUH KEPERCAYAAN PADA MANAJER TERHADAP MOTIVASI KARYAWAN DALAM KEHIDUPAN BISNIS: SEBUAH PENELITIAN PADA KARYAWAN RAMAYANA - Dadang Purwo Ariwidodo (Media Mahardhika, 2020)
Many factors influence employee work motivation at the individual and organizational level, both internally and externally, psychosocially and physiologically. The trust aspect, which is also the foundation of interhuman relationships, is undoubtedly one of the most significant factors. Trust depends on the circumstances of the individual and the company. Confidence at the person level in general can be assured if the employee has a tendency to be confident and behave and behave. Trust at the organizational level can only be guaranteed if decisions and practices within the organization can be trusted, especially all managerial activities and actions. In Ramayana, Surabaya,field studies were conducted and384 participants, according to the sample size, were involved in the study. There is a positive correlation between employee motivation and trust according to the results. The most powerful factor among managers' trust factors is that managers are honest in their activities and actions. On the other hand, intrinsic motivation is the most important driving force. Therefore, this research shows that trust in managers has a positive influence on employees' work motivation.